2017
DOI: 10.1038/ncomms15617
|View full text |Cite
|
Sign up to set email alerts
|

Codon bias imposes a targetable limitation on KRAS-driven therapeutic resistance

Abstract: KRAS mutations drive resistance to targeted therapies, including EGFR inhibitors in colorectal cancer (CRC). Through genetic screens, we unexpectedly find that mutant HRAS, which is rarely found in CRC, is a stronger driver of resistance than mutant KRAS. This difference is ascribed to common codon bias in HRAS, which leads to much higher protein expression, and implies that the inherent poor expression of KRAS due to rare codons must be surmounted during drug resistance. In agreement, we demonstrate that prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 50 publications
1
38
0
Order By: Relevance
“…In contrast, biochemical properties of different KRAS alleles likely contribute to allele selection over a broad spectrum of cancer types (Figure 3E). Other aspects of allele selection are less well characterized (see Outstanding Questions), for example whether KRAS expression level matters, as suggested recently in studies of codon usage [71]. In the end, the “how?” and “why?” of allele choice are less important than the “so what?”.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, biochemical properties of different KRAS alleles likely contribute to allele selection over a broad spectrum of cancer types (Figure 3E). Other aspects of allele selection are less well characterized (see Outstanding Questions), for example whether KRAS expression level matters, as suggested recently in studies of codon usage [71]. In the end, the “how?” and “why?” of allele choice are less important than the “so what?”.…”
Section: Discussionmentioning
confidence: 99%
“…The resistance mechanism to cetuximab shown by many tumor types remains unclear, although KRAS mutation, as well as EGFR mutation and HER2 or MET activation, has been implicated [15][16][17][18][19][20][21][22]. HRAS mutation or upregulated expression of microRNA-100 and microRNA-125b have also been shown to be associated with cetuximab resistance [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…We had previously demonstrated that ectopic expression of KRAS* generated more protein than KRAS in a variety of cell types (9,39,40). However, the contribution of changing rare codons to common on KRAS mRNA levels in different cells,…”
Section: The Differential Effects Of Codon Usage On Kras Expression Imentioning
confidence: 99%
“…Moreover, such changes had in vivo phenotype, namely altering the proliferation of hematopoetic stem cells or affecting various stages of tumorigenesis (9,39,40). However, the contribution of codon bias to the various steps in KRAS protein production had not been systematically examined.…”
mentioning
confidence: 99%